2019
DOI: 10.1167/19.6.16
|View full text |Cite
|
Sign up to set email alerts
|

Motion direction, luminance contrast, and speed perception: An unexpected meeting

Abstract: Motion direction and luminance contrast are two central features in the representation of visual motion in humans. In five psychophysical experiments, we showed that these two features affect the perceived speed of a visual stimulus. Our data showed a surprising interaction between contrast and direction. Participants perceived downward moving stimuli as faster than upward or rightward stimuli, but only at high contrast. Likewise, luminance contrast produced an underestimation of motion speed, but mostly when … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 50 publications
2
9
0
Order By: Relevance
“…Also, when viewing a target that oscillates back-and-forth along a circular arc, observers perceive as uniform only kinematic profiles close to harmonic motion, consistent with the assumption of a pendulum accelerated by gravity (La Scaleia et al, 2014b). Moreover, stimuli moving downward at constant speed are perceived as faster than stimuli moving upward or rightward, consistent with the hypothesis that observers combine sensory measurements with a prior assumption of approximate gravity effects (Moscatelli et al, 2019). In addition, if the visual scene is rich of contextual cues providing an environmental reference and scale, the discrimination of time duration of accelerated targets is more precise for downward motion than for upward or horizontal motion (Moscatelli and Lacquaniti, 2011).…”
Section: Introductionsupporting
confidence: 60%
“…Also, when viewing a target that oscillates back-and-forth along a circular arc, observers perceive as uniform only kinematic profiles close to harmonic motion, consistent with the assumption of a pendulum accelerated by gravity (La Scaleia et al, 2014b). Moreover, stimuli moving downward at constant speed are perceived as faster than stimuli moving upward or rightward, consistent with the hypothesis that observers combine sensory measurements with a prior assumption of approximate gravity effects (Moscatelli et al, 2019). In addition, if the visual scene is rich of contextual cues providing an environmental reference and scale, the discrimination of time duration of accelerated targets is more precise for downward motion than for upward or horizontal motion (Moscatelli and Lacquaniti, 2011).…”
Section: Introductionsupporting
confidence: 60%
“…Thus, the additional context provided by the virtual environment may have influenced participants’ speed judgements beyond what may be predicted by simple low-level visual features. Recently, Moscatelli et al ( 2019 ) suggested that biases in perceived speed may be influenced by priors for motion dynamics within a scene, which may depend on factors such as gravity and the scene medium (i.e., water or air). Accordingly, downwards moving targets with high luminance contrast were perceived as faster than upwards moving and lower contrast targets (Moscatelli et al 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Moscatelli et al ( 2019 ) suggested that biases in perceived speed may be influenced by priors for motion dynamics within a scene, which may depend on factors such as gravity and the scene medium (i.e., water or air). Accordingly, downwards moving targets with high luminance contrast were perceived as faster than upwards moving and lower contrast targets (Moscatelli et al 2019 ). Similarly, semantics concerning the object may also have influenced the expected motion dynamics of the scene, affecting speed biases independently from the gravitational advantage.…”
Section: Discussionmentioning
confidence: 99%
“…Speed perception and distance perception are the two main topics related to driving behavior in foggy weather. As described in the second paragraph of the introduction, most studies in this field have focused on speed perception 2 , 3 , 6 8 , 10 , 14 , 41 , 42 and ultimately confirmed an overestimation effect of speed 2 . Admittedly, this overestimation effect of speed makes sense.…”
Section: Discussionmentioning
confidence: 84%